REPRESENTING THE ISLAMIST POLITICS IN BANGLADESHI NEWSPAPERS: THE 2023 BARISHAL CITY CORPORATION ELECTION AS A CASE - Mia, Md. Rana (PEOPLE: International Journal of Social Sciences, 2024)
This study aims to explore the representation and news coverage of an Islamist political party- Islami Andolon Bangladesh (IAB) in three Bangladeshi mainstream and ‘quality’ daily newspapers- the Daily Star (DS), the Daily Janakantha (DJ) and the New Age (NA). In the context of the city corporation election- the 2023 Barishal City Corporation (BCC), the study has been conducted. It examines if the dailies either sidelined, ignored or favored this Islamist party. It observes where they pay more or less news value about IAB and its electoral campaign. Additionally, it argues that the candidate of IAB used myth through speeches to encourage voters. The myth— if you vote for hand-fan (electoral symbol of IAB), Allah and his messenger (prophet Hazrat Muhammad) will have the votes —was unchallenged and unquestioned and the advice not to use misinformation and misguide the voters found absent in the dailies. Though the IAB could not win the election, it was expected that mass media as social institutions would come forward with accurate information to inform people wisely and so that ordinary people would not be misguided. Through quantitative and qualitative content analysis, this study leads to the outcomes that these newspapers were silent to uphold the activities of IAB. The DS and DJ had a propensity to sideline and ignore the IAB and its electioneering despite receiving the second highest vote in the election. They prioritized ruling party Awami League (AL) and Jatiya Party (JaPa) while the NA prioritized IAB through providing a better representation and emphasizing on different allegations made by this party. In future, this research can be a basement or pioneer for the researchers who will intend to look into the perspective of newspapers on political parties